UJI AKTIVITAS ANTIJAMUR SEDIAAN KRIM EKSTRAK ETANOL DAUN CIPLUKAN (Physalis angulata L.) TERHADAP Candida albicans - Salsabila Khairunnisa; Endang Setyowati; Muhammad Nurul Fadel; Arif Fahrudin (IJF (Indonesia Jurnal Farmasi), 2021)
Background : Infectious diseases are one of the problems that often occur in Indonesia. One of the most common infections is an infection caused by the fungus  Candida albicans. The incidence of antifungal resistance has become a problem so that new innovations are needed. One of them is the development of medicinal plants that have been studied to have antifungal properties. One of them is the Ciplukan plant (Physalis angulata L.). Ciplukan leaves contain active compounds in the form of alkaloids, saponins, tannins, and flavonoids which are biologically active compounds as antimicrobials. Objective: To determine the antifungal activity of the ethanol extract of Ciplukan leaf (Physalis angulata L.) cream against the fungus Candida albicans. Methods: This study used disc diffusion with concentrations of 5%, 10%, and 15% placed on SDA media that had been overgrown with Candida albicans which would then be incubated and the diameter of the inhibition zone was measured. Results: At a concentration of 5% on day 1 and day 21, the diameter of the inhibition zone was 15 mm and 14 mm, 10% concentration got results on day 1 18 mm and day 21 was 15 mm, then 15% concentration on day 1 1st and 21st got a result of 20 mm, and the positive control got a result of 34 mm on day 1 and on day 21 got 33 mm. Conclusion: Based on the data above, it can be concluded that the cream of ethanol extract of Ciplukan leaves (Physalis angulata L.) can inhibit the fungus Candida albicans. Keywords: Ciplukan Leaf, Candida albicans, Antifungal Activity